Tolerance of ALL Induction Therapy in Children with Limited Resources: A Retrospective Study from a Teaching Hospital - Tanvi Khanna (Journal of Clinical and Diagnostic Research, 2022)
Introduction: Acute Lymphoblastic Leukaemia (ALL) is the most common malignancy in children. Due to the better understanding of biology, intensive multi-agent chemotherapy and improved supportive care, ALL is curable in majority of children. Induction phase is the most intense and critical phase of therapy. Aim: To examine the feasibility of high-intensity induction and its tolerance in a resource-limited setting in children with acute lymphoblastic leukaemia. Materials and Methods: This retrospective analysis was done on children admitted for ALL treatment. Data was collected for January 2016 to July 2018, regarding baseline characteristics, tolerance to induction therapy, morbidity, mortality, deviations from protocol, and induction outcomes among children with ALL treated at a tertiary care teaching hospital (Cancer Research Institute, Himalayan Institute of Medical Sciences, Dehradun, Uttrakhand, India). Confirmed cases of ALL with age upto 18 years, who took more than a week of planned induction were included in the study. Data was analysed using Chi-square and Fisher’s-exact test. Results: Four-drug induction was feasible and given to 76 patients during the study period. Mean age of the group was 9.3 years. Male: female ratio was 1.3:1. Remission was achieved in 63 (82.8%) patients. Four deaths occurred, and were attributed to infection. Hyperglycaemia (4), CNS events (2), peripherally inserted central line related thrombosis (2) and pulmonary tuberculosis (1) were noted. Febrile neutropenia was noted in 65 cases and seven cases required ICU care; two of them succumbed in the ICU. Baseline blood parameters, subtype of disease, protocol of treatment and age did not affect the induction outcome statistically. Conclusion: Intensive induction chemotherapy has varying complications and can be employed even in resource-limited settings with acceptable results.